Evaluation on the installation of the automatic lane barriers (alb) by campus community - Abdul Rahman, Mahfuzah; Abdul Kadir, Hasnah; Wok, Saodah (GIAP Journals, 2018)
Purpose of the Study: This study examines the evaluation of Automatic Lane Barriers (ALB) system implementation on the campus community. The objectives of this study are to identify the differences between male and female on their evaluations towards the ALB system; and to determine the differences between staff and student on their attitude, behaviour, perceived usefulness (PU), and perceived ease of use (PEU) towards the ALB system. Methodology: This study applies the quantitative research design using the survey method where self-administered questionnaires are used as the instrument for data collection. A total of 271 respondents participated in this study. Main Findings: The findings show that, on the whole, campus community have a positive evaluation pertaining to perceived usefulness of the ALB system implementation only. There is no significant difference between male and female respondents on all variables while there are significant differences between staff and student towards the ALB system for all variables concerned. Applications of this Study: This study adapted the items in the Technology Acceptance Model (TAM) to a newly implemented Automatic Lane Barriers (ALB) installation to differentiate the acceptance of ALB system according to gender and designation. The main reason for such implementation is to increase security and safety measures for the campus community. Novelty/Originality of this Study: This study is done immediately after the ALB is enforced. Thus, the findings act as the benchmark for the acceptance of any new innovation for the campus community in the future.